A Symbolism Analysis of the Deadly Sins of the Saja Boys from the K-Pop Demon Hunter Movie - Putri Rindu Kinasih (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The animated film KPop Demon Hunters quickly became a worldwide hit, reaching the top of Netflix's global charts with over 33 million views in just two weeks. The highly acclaimed film KPop Demon Hunters has been the subject of some research due to its notable accomplishment. Yet, none of the research above discusses the symbolism that is richly put in the movie. Thus, the research attempts to elaborate on the representation of symbolism in order to provide an alternative viewpoint of the Kpop Demon Hunters, particularly the well-known villain, the Saja Boys. In order to study the underlying meaning of the Saja Boys, the author employs the qualitative method and applies Vrabel's study of deadly sin in relation to the religious symbol. This study concludes that the members of the Saja Boys represent symbolism of the deadly sins, which are anger, envy, greed, lust, pride, gluttony, and sloth. These vices are shown from the behavior of the Saja Boys, such as barking towards fans aggressively, being envious of one’s freedom and happiness, stocking food as much as possible, giving sexual gratification through physical appearance, and being overly proud of it. Not only that, the members of Saja Boys also portrayed the action of overconsumption and laziness.